CRIMINOLOGICAL CHARACTERISTICS AND PREVENTION OF SUICIDE AMONG MILITARY PERSONNEL - Zvonenko, O.; Bury, S. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
It has been found that suicide in Ukraine is the seventh leading cause of death, which confirms the criticality of the problem and the need to solve it as soon as possible. Today, there is a need to support such categories of people as children and youth, servicemen, convicts and the elderly. The need to unite the efforts of all services that ensure the viability of military units was identified. The study of suicide in the armed forces has shown that suicide prevention is comprehensive and can only be addressed through the joint efforts of physicians, psychologists, social workers, commanders of all levels and officers of educational institutions. It has been found that suicide is usually carried out of desperation, in protest to preserve self-esteem, as a result of obscuration of the mind to avoid pain or revenge. Poverty, unemployment, loss of loved ones and problems in family relationships are also areas at risk of voluntary death and, most importantly, experts do not have the full amount of accurate statistics on the number of "successful" attempts to leave this world. The increased social danger and high latency of suicide of servicemen have been determined. It is emphasized that the criminal law subgroup consists of determinants, which, unlike most general social determinants, arise from the direct influence of some individuals on others and the main complication is that such influence is intentional, covered by cruel, immoral nature of in connection with which entails socially dangerous consequences. The main reasons and conditions that contribute to suicide are named. It is proved that suicide prevention in the Armed Forces of Ukraine should be based on knowledge of probable causes and their elimination. The basis of prevention is high morality. It is necessary to achieve the utmost respect for others, taking into account personal dignity. Conduct educational work, including religious education.
Keywords: war crimes, suicide, serviceman, prevention, globality of the problem, dynamics, traumatic retirement